2015
DOI: 10.1134/s1063780x15090019
|View full text |Cite
|
Sign up to set email alerts
|

Determination of a brass alloy concentration composition using calibration-free laser-induced breakdown spectroscopy

Abstract: Laser-induced breakdown spectroscopy (LIBS) is a technique that can provide qualitative and quantitative measurements of the сharacteristics of irradiated metals. In the present work, we have calculated the parameters of the plasma produced from a brass alloy sample under the action of a pulsed Nd : YAG laser operating at 1064 nm. The emission lines of copper atoms (Cu I), zinc atoms (Zn I), and lead atoms (Pb I), which are elements of a brass alloy composition, were used to investigate the parameters of the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…The intensity ratio for Fe I/ Fe I was 0.6 and their transition ratio was 0.604. The consistency between the intensities of Ca, Fe, Si and with their corresponding transition probability was observed, which clearly supported the assumption of optically thin laser induced plasma [14]. In local thermal equilibrium condition, the collision process predominate the radiative process, which ensures that the energy exchange between the species is larger than the energy lose due to the radiation.…”
Section: Calibration Free Assumptionssupporting
confidence: 72%
“…The intensity ratio for Fe I/ Fe I was 0.6 and their transition ratio was 0.604. The consistency between the intensities of Ca, Fe, Si and with their corresponding transition probability was observed, which clearly supported the assumption of optically thin laser induced plasma [14]. In local thermal equilibrium condition, the collision process predominate the radiative process, which ensures that the energy exchange between the species is larger than the energy lose due to the radiation.…”
Section: Calibration Free Assumptionssupporting
confidence: 72%
“…In [4,6], authors present the results of detection of heavy metals in soil samples [4] and metals [6] by laser spectroscopy method. Comparison of the given results to the traditional chemical methods demonstrated high accuracy of laser spectroscopy and optical instruments, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of the given results to the traditional chemical methods demonstrated high accuracy of laser spectroscopy and optical instruments, respectively. In [6], it has been specified that laser spectroscopy is a method, which can provide quantitative and qualitative measurement of the characteristics of irradiated metals. Authors in [6] calculated plasma parameters, which have been given from the sample of brass alloy by pulse of Nd:YAG laser.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although LIBS based studies on brass alloys having different compositions have been reported in the literature [24][25][26][27][28], the main objectives of the present work are to exploit the LIBS techniques for the quantitative analysis of a brass alloy containing copper and zinc of known compositions, 62% and 38%, respectively, and to compare the extracted results with the certified compositions, as well as with that determined using well established analytical techniques such as x-ray spectroscopy (EDX) and laser ablation time-of-flight mass spectrometry (LA-TOF-MS). It is observed that the IRSAC results are in good agreement with the certified compositions and that of the EDX and LA-TOF-MS results.…”
Section: Introductionmentioning
confidence: 99%